Feasibility of sustainable nitrogen removal: integration of partial nitritation-anammox with membrane aerated biofilm reactor (MABR) - Shiu, Natalia (My University, 2023)
The presence of nutrients, such as nitrogenous compounds, in wastewater can pose serious environmental concerns to water systems leading to reduced water quality and potential risks to the public health. Nutrient removal in conventional wastewater treatment systems is becoming increasingly more costly due to the extensive energy requirements and high aeration costs. Anaerobic ammonium oxidation (Anammox) is an alternative method for nutrient removal which can reduce overall treatment costs due to less aeration requirements and less sludge production. Anammox process can be implemented with other innovative technologies, such as membrane aerated biofilm reactors (MABR) to achieve effective and sustainable nutrient removal. A major challenge associated with Anammox process is effective control of nitrite oxidizing bacteria (NOB). High temperature in wastewater treatment systems can promote Anammox bacterial growth and inhibit NOB activity. This research aims to investigate the feasibility of integrating Anammox processes with MABR technologies and to examine the effects of high temperature aeration supplied to MABR systems on Anammox bacterial growth and NOB suppression. The nitrogen removal by Anammox bacteria in a lab-scaled MABR is examined to determine the impact of aeration temperature on inhibition of NOB.
Keywords: anaerobic ammonium oxidation (anammox); membrane aerated biofilm reactor (MABR); sustainable nitrogen removal